1999
DOI: 10.3168/jds.s0022-0302(99)75276-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Vitamin E and Selenium During the Dry Period on Mammary Health and Milk Cell Counts in Dairy Ewes

Abstract: The effect of parenteral administration of two subcutaneous injections of vitamin E and Se (5 mg and 0.1 mg/kg of body weight, respectively) during the dry period on the mammary health and milk somatic cell counts of 25 dairy ewes was investigated. Supplementation reduced somatic cell counts (5.4 vs. 6.0 log10) during the subsequent lactation but had no effect on the incidence of clinical mastitis (4% vs. 6%) and intramammary infections (9.0% vs. 11.3%). Furthermore, the administration of vitamin E and Se was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
4
20
1
7
Order By: Relevance
“…In agreement with previous work (Weiss et al, 1990;Morgante et al, 1999), increased maternal Se decreased colostrum SCC. Later in lactation, gestational Se supply had no effect on SCC, whereas ewes that were restricted during gestation had fewer somatic cells than controls.…”
Section: Colostrum and Milk Nutrient Compositionsupporting
confidence: 93%
“…In agreement with previous work (Weiss et al, 1990;Morgante et al, 1999), increased maternal Se decreased colostrum SCC. Later in lactation, gestational Se supply had no effect on SCC, whereas ewes that were restricted during gestation had fewer somatic cells than controls.…”
Section: Colostrum and Milk Nutrient Compositionsupporting
confidence: 93%
“…Especially in the case of sheep fed in pasture, it has been found that the combination of estrus synchronization with Se and Vit E supplementation may increase the fertility rate (3,16). Se and Vit E protect biological membranes against oxidative degeneration and are an essential component of glutathione peroxidase (15,20). It has been reported that intravaginal progesterone sources used for estrus synchronization in farm animals cause an increase in oxidative stress parameters (19,21,25).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…In dairy ewes, parenteral administration of vitamin E and selenium during the dry period can reduce SCC and increase the percentages of milk neutrophils during the subsequent lactation [102,121]. Sensitivity may also be increased by milk retention, due to a bad working milking machine, under-milking, stressful or painful milking and even udder morphology.…”
Section: Environmental Factorsmentioning
confidence: 99%